The Efficacy of Mannitol Combined with 6-Aminocaproic Acid in the Treatment of Patients with Cerebral Hemorrhage and Its Impact on Immune Function. (12th July 2022) - Tian, Buxian; Tian, Bohan; Zhang, Yuhong
Abstract : Objective . To determine the efficacy of Mannitol combined with 6-aminocaproic acid in the treatment of patients with cerebral hemorrhage, as well as its impact on the immune system. Methods . The study subjects consisted of 122 patients with early intracerebral hemorrhage treated in our hospital from April 2019 to April 2022. Based on the different admission times, the participants were randomly divided into the control group and the study group in a ratio of 1:1. 6-Aminocaproic acid was used to treat patients in the control group, while Mannitol along with 6-aminocaproic acid was used to treat patients in the study group. Short form-36 health survey (SF-36) scores, hematoma volume changes, National Institutes of Health Stroke Scale (NIHSS), and Mini-Mental State Examination (MMSE) scores, clinical efficacy, and changes in the immune function in patients from the two groups were analyzed and compared. Results . The total efficacy of treatment in the study group was significantly higher than that in the control group ( x 2  = 9, 375, P < 0.001 ). Patients in the study group had significantly higher scores in social function, mental health, physical function, and physiological function compared to those in the control group (P < 0.05 ). After treatment, there was a significant reduction in NIHSS scores in patients from both groups, but a greater reduction was seen in patients from the study group (P < 0.05 ). After 2 weeks of treatment, the volume of cerebral edema was significantly smaller in patients from the study group than in those from the control group (P < 0.05 ). Before treatment, there was no significant difference in the number of CD4+ and CD8+ T lymphocytes between patients in the two groups. However, after treatment, patients in the study group had higher numbers of CD4+ T lymphocytes and lower numbers of CD8+ T lymphocytes compared to those in the control group (P < 0.05 ). Conclusions . The combination of Mannitol and 6-aminocaproic acid appears to be very efficacious in the treatment of cerebral hemorrhage. It improves immune function, reduces neurological damage, and minimizes the volume of cerebral edema.